Evangelization in Cyberspace for the Promotion moral Development of the Nigerian Youths - Orlu, Hyacinth Chimene (Advances in Social Sciences Research Journal, 2016)
Concerned for the moral decrepitude of the Nigerian society, especially among the youths, this paper takes a look at how evangelizing activities in cyberspace can be used to improve the moral life of the youths. To accomplish this objective, the work defines and explicates the concept of morality, makes a historical incursion into the act of moral living among Nigerians, discusses some immoral practices among the youths and establishes the need for their moral development. For the morals of the youths to appreciate, the paper postulates evangelization of the youths in the realm of the social media that make up the cyberspace – the technological space which the paper adequately describes. Concluding, the paper explains the various areas in which the cyberspace is strong in evangelizing. The evangelical practices which can help instill morals in the youths are thus pointed out.